2021
DOI: 10.1039/d0cc07740b
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome-mediated incorporation of fluorescent amino acids into peptides in vitro

Abstract: We report the design, chemical synthesis, and flexizyme-catalyzed transfer RNA (tRNA) acylation of a variety of fluorescent amino acids (FAAs). The fluorescent groups include pyrene, coumarin, nitrobenzoxadiazole, and fluorescein variants....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 43 publications
0
30
0
Order By: Relevance
“…Straightforward assays are therefore required to assess the permeability of promising leads, with fluorescence imaging being a popular approach. Typically, peptide leads are appended with a fluorophore (e. g. FITC, TAMRA, Rhodamine) to assess cell permeability [5] . Whilst widely used, these strategies use the labelled peptide as a proxy for the untagged version of the molecule.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Straightforward assays are therefore required to assess the permeability of promising leads, with fluorescence imaging being a popular approach. Typically, peptide leads are appended with a fluorophore (e. g. FITC, TAMRA, Rhodamine) to assess cell permeability [5] . Whilst widely used, these strategies use the labelled peptide as a proxy for the untagged version of the molecule.…”
Section: Methodsmentioning
confidence: 99%
“…Typically, peptide leads are appended with a fluorophore (e. g. FITC, TAMRA, Rhodamine) to assess cell permeability. [5] Whilst widely used, these strategies use the labelled peptide as a proxy for the untagged version of the molecule. This can result in misleading findings where the fluorophore changes the physicochemical properties of the parent peptide and influences their ability to penetrate and localize in cells.…”
mentioning
confidence: 99%
“…In one recent study, four chemically diverse non-canonical scaffolds (phenylalanine, benzoic acid, heteroaromatic, and aliphatic acid analogs) were investigated for the compatibility of their substrates with the three flexizymes (Lee et al, 2019). Based on the molecular characteristics and yields in Fx-catalyzed reaction in several studies (Lee et al, 2021(Lee et al, , 2020b(Lee et al, , 2019(Lee et al, , 2020cPassioura and Suga, 2014;Rogers et al, 2018;Tsiamantas et al, 2020), several general substrate design rules were identified for efficient tRNA charging (Figure 4E). First, substrates with a similar molecular structure to…”
Section: Genetic Code Reprograming In Vitromentioning
confidence: 99%
“…Taken together, numerous non-canonical substrates have now been acylated to tRNA by Fx and subsequently incorporated site-specifically into a peptide in a reconstituted PURE system. The substrates include a- (Obexer et al, 2017), b-(Fujino et al, 2016, g- (Ohshiro et al, 2011), D-amino acids (Katoh et al, 2017) Review (Lee et al, 2021), non-amino (aromatic, aliphatic) acids (Lee et al, 2019), foldamers Rogers et al, 2018), oligomeric peptides (Tsiamantas et al, 2020), malonyl (polyketide-like) acids (Ad et al, 2019), hydroxyacids (Ohta et al, 2007(Ohta et al, , 2008, and thioacids (Takatsuji et al, 2019).…”
Section: Reviewmentioning
confidence: 99%
“…FITC, TAMRA, Rhodamine) to assess cell permeability. [5] Whilst widely used, these strategies use the labelled peptide as a proxy for the untagged version of the molecule. This can result in misleading findings where the fluorophore changes the physicochemical properties of the parent peptide and influences their ability to penetrate and localize in cells.…”
mentioning
confidence: 99%